Evolution from protoplanetary to debris discs: the transition disc around HD 166191 - Kennedy, Grant M.; Murphy, Simon J.; Lisse, C. M.; Ménard, F.; Sitko, M. L.; Wyatt, M. C.; Bayliss, D. D. R.; DeMeo, F. E.; Crawford, K. B.; Kim, D. L.; Rudy, R. J.; Russell, R. W.; et al. (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. HD 166191 has been identified by several studies as hosting a rare and extremely bright warm debris disc with an additional outer cool disc component
Gesehen am 21.09.2020